NIMG-67. CLINICAL APPLICATIONS OF QUANTITATIVE THREE-DIMENSIONAL MRI ANALYSIS FOR PEDIATRIC EMBRYONAL BRAIN TUMORS. (5th November 2018) - Hara, Jared; Wu, Ashley; Villanueva-Meyer, Javier; Valdes, Gilmer; Daggubati, Vikas; Mueller, Sabine; Solberg, Timothy; Braunstein, Steve; Morin, Olivier; Raleigh, David
Abstract: OBJECTIVES: Pediatric embryonal brain tumors include medulloblastoma, supratentorial primitive neuroectodermal tumor, and pineoblastoma. The purpose of this study was to investigate the prognostic utility of quantitative three-dimensional (3D) magnetic resonance imaging (MRI) radiomic analysis for primary pediatric embryonal brain tumors. METHODS: Thirty-four pediatric embryonal brain tumor patients with concurrent pre-operative T1-weighted post contrast (T1PG) and T2-weighted fluid-attenuated inversion recovery (FLAIR) MR images were identified from an institutional database. The median imaging follow-up was 5.2 years. Radiomic features were extracted from axial T1PG and FLAIR contours using MATLAB, and 15 features were selected for analysis based on qualitative radiographic features with known prognostic significance for pediatric embryonal brain tumors. Logistic regression, linear regression, receiver operating characteristic curve, Harrells C index and Somers D index were used to test the relationships between radiomic features, demographic variables and clinical outcomes. RESULTS: We found that pediatric embryonal brain tumors in older patients had increased normalized mean tumor intensity (P=0.05, T1PG), decreased tumor volume (P=0.02, T1PG) and increased markers of heterogeneity (P0.01, T1PG and FLAIR) relative to younger patients. We identified 10 quantitative radiomic features that delineated between medulloblastoma, pineoblastoma and supratentorial primitive neuroectodermal tumor, including size and heterogeneity (P0.05, T1PG and FLAIR). Decreased markers of tumor heterogeneity were predictive of neuraxis metastases and trended towards significance (P=0.1, FLAIR). Tumors with increased size (AUC=0.7, FLAIR) and decreased heterogeneity (AUC=0.7, FLAIR) at diagnosis were more likely to recur. CONCLUSIONS: Quantitative radiomic features are associated with pediatric embryonal brain tumor patient age, histology, neuraxis metastases and recurrence, and could be used for risk stratification.